Lethal legacy : a novel - Fairstein, Linda A. (New York : Anchor Books, 2009)
Assistant district attorney Alex Cooper and her crew are drawn into the strange and privileged world of rich collectors, eccentric library trustees, and the treasures of the great New York Public Library after a librarian disappears and a woman's corpse turns up in the missing librarian's abandoned apartment.
Keywords: New York Public Library -- Fiction; Cooper, Alexandra (Fictitious character) -- Fiction; Public prosecutors -- Fiction; Map collections -- Fiction; New York (N.Y.) -- Fiction; New York (State) -- Fiction; Mystery fiction